Water Resources Management (WRM) : Strengthening Climate-Informed Project Design - World Bank Water Global Practice; Global Water Security and Sanitation Partnership (Washington, DC, 2022)
As climate shocks increasingly impact the water dependent sectors, it is vital that countries embrace integrated, cross-sectoral policies and programs. Water projects improve chances to attain positive climate-related and overall results by adopting an integrated and climate-informed approach to water resources management (WRM), carefully managing climate-related environmental and social safeguards and establishing effective coordination mechanisms based on incentives with all relevant stakeholders.